Visual programming environment based on data visualization grammar specification - Ivanov, Egor; Khoroshavin, Aleksandr; Karsakov, Andrey (Procedia computer science, 2020)
This paper presents a web-based platform for construction and execution of data visualization workflow. The environment enables construction of data visualization workflow with the visual programming interface and provides the ability of previewing the visualisation workflow result in real-time. The use of visual programming makes the workflow composition faster and it’s also lowers entry threshold for the process of data visualization. In this paper we discuss the architecture and main building blocks of the data visualization workflow.